Peningkatan Kapasitas Peternak Kambing Peranakan Etawa Skala Kecil melalui Penerapan Sistem Recording dan Pemilihan Bibit Unggul - Budi Irwanto Julia Firda; Umi Kalsum; Badat Muwakhid (Jurnal Pengabdian Masyarakat Indonesia (JPMI), 2026)
Small-scale Peranakan Etawa (PE) goat farming still faces low productivity due to limited farmers’ capacity in livestock management, particularly in the application of recording systems and the selection of superior breeding stock. This community service program aimed to enhance farmers’ capacity by implementing a simple livestock recording system and data-based selection of superior PE goat breeding stock. The activity was conducted with the “Maju Bersama” Farmer Group in Toyomarto Village, Singosari District, Malang Regency, involving 20 goat farmers. The methods included extension activities, interactive discussions, and hands-on field mentoring, which improved farmers’ knowledge and skills in applying livestock recording systems and in utilizing recorded data to select livestock, focusing on recording identity, reproduction, production, and health data. The results showed an improvement in farmers’ knowledge and skills in applying livestock recording systems and utilizing recorded data as a basis for selecting superior breeding stock. The implementation of a simple recording system was considered easy to adopt and supported decision-making in livestock management. This program contributes to strengthening farmers’ capacity, improving genetic quality, and enhancing the productivity of PE goats in small-scale farming systems in a sustainable manner.